FAKTOR-FAKTOR YANG MEMENGARUHI KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH SURABAYA - Andajani, Andajani; Hamen, Nataly Feraty Nadia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This research aimed to obtain empirical evidence (1) The effect of internal control on the employees’ performance, (2) The effect of human resources competency on the employees’ performance; (3) The effect of information technology advantage on the employees’ performance at the Regional Financial and Asset Management Agency (BPKAD) Surabaya. This research was conducted quantitatively with population used by employees of the Regional Financial and Asset Management Agency (BPKAD) Surabaya. Furthermore, the sampling technique used 47 employees. Then, the data used is primary data taken from questionnaires distributed to the employees of the Regional Financial and Asset Management Agency (BPKAD) Surabaya. Moreover, the research analysis method used multiple linear regression. As a result, the research indicates that (1) Internal control had a positive effect on the employees’ performance; (2) Human resource competency had a positive effect on the employees’ performance; (3) The advantage of information technology did not affect the employees’ performance.